POTENCIAL ZOONOTIC PARASITES FOUND IN SIX SWINE FARMS OF CUNDINAMARCA, COLOMBIA - Pulido-Villamarín, Adriana (2013)
In Colombia, the departments of Cundinamarca, Huila and Tolima, among others, represent 19.16% of the total domestic production of pig farms. Gastrointestinal parasites (PGI) limit the productive potential of infected animals, affecting parameters such as average daily gain and food conversion ratio. The aim of the study was to determinate the prevalence of PGI with a zoonotic potential in backyard farms and semi-technical production. Farmyard pigs were sampled in three semi-technified farms with full production cycle (breeding, fattening and lift) in the municipalities of Vega, Chia, Tibirita and in four backyard pig farms (fattening) in the towns of Chía and Santandersito. The farms were chosen for convenience. Three samplings were performed serially at intervals of 15 days and analyzed with a total of 119 samples, 94 farms and 25 semi-technified backyard farms. Stool samples in "pool" per pen, were analyzed by direct analysis, qualitative flotation technique and staining with modified Ziehl-Neelsen. In semi-technified farms, Balantidium coliMalmsten, 1857 cysts (40.5%), Giardiaspp. (26.9%) cysts, Balantidium colitrophozoites (3.5%), Eimeriaspp. (3.8%), eggs of Anoplocephalidaeeggs (1.8%), hepatic Fasciolaeggs (2.0%), Ascaris suumGoeze, 1782 eggs (0.6%), cysts of Entamoeba(1.5%) and larvae of Strongyloidesspp. (0.3%) were detected. In backyard farms we found cysts of Entamoebaspp. (42.5%), cysts of Giardiaspp. (30%), Blastocystis spp (37.5%) and Taenia soliumLinnaeus, 1758 eggs (2.5%). The presence of Giardia, Entamoebaand Blastocystissuggests the possible transmission of parasite populations between pigs and humans thus increasing the transmission of parasites zoonotic potential.